AIRCRAFT GROUND ICING AND DE-ICING PROCESSES AS MECHANISMS OF THE MOTION IN MIRCE MECHANICS - Knežević, Jezdimir (Journal of Applied Engineering Science, 2015)
Mirce Mechanics is a scientific theory of the motion of in-service systems through Mirce Spacetime that enables prediction of the work done by them to be made by using Mirce Equations. However, practical applications of Mirce Mechanics are possible only, when the physical mechanisms that generate the motion of systems through positive and negative states are understood. The mechanism of ice building on an aircraft on the ground is addressed in this paper, as a cause of occurrence of a negative in-service event. It is generated under certain environmental conditions when precipitation falling onto the aircraft freezes, mainly on upper surfaces of the wing and tail, endangering the flight safety. This type of negative events is followed by de-icing process of the aircraft at the airport, as a physical mechanism that causes the transition of an aircraft from the negative to the positive in-service state. Several de-icing methods are presented in this paper together with the analysis of their impacts on aircraft and environment.